Transformasi Hak Kekayaan Intelektual sebagai Objek Wakaf: Kajian Normatif dan Implementasi berdasarkan Prinsip Hukum Islam - Widjaja, Abdi; Qalbi, Nur; Bakry, Muammar (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study aims to analyze the transformation of intellectual property rights (IPR) as an object of waqf in the perspective of Islamic law, with a focus on normative studies and their implementation in contemporary practice. The main issue raised is the extent to which IPR, as an intangible asset, can be accepted within the framework of Islamic law as an object of waqf, as well as the challenges that arise in the implementation process. This study uses a qualitative method based on literature studies, with a normative approach to review the provisions of classical and modern Islamic law, as well as analysis of regulations related to waqf and IPR. The results of the study show that IPR meets the criteria of sharia as an object of waqf, especially in the framework of sharia maqasid which focuses on the protection of assets (hifzul maal) and the achievement of the benefits of the people. However, the implementation of IPR waqf still faces obstacles, such as the lack of specific regulations, limited public understanding, and obstacles in the management and distribution of its benefits. The implications of this study emphasize the importance of updating the waqf law to include IPR as one of the waqf assets, accompanied by strengthening the management capacity and synergy between religious institutions, the government, and the community. This transformation is expected to be able to expand waqf's contribution to science-based economic development and increase the sustainability of social benefits.